Numerical Simulation and Response of Stiffened Plates Subjected to Noncontact Underwater Explosion. (28th August 2014) - Fathallah, Elsayed; Qi, Hui; Tong, Lili; Helal, Mahmoud
Abstract : A numerical simulation has been carried out to examine the response of steel plates with different arrangement of stiffeners and subjected to noncontact underwater explosion (UNDEX) with different shock loads. Numerical analysis of the underwater explosion phenomena is implemented in the nonlinear finite element code ABAQUS/Explicit. The aim of this work is to enhance the dynamic response to resist UNDEX. Special emphasis is focused on the evolution of mid-point displacements. Further investigations have been performed to study the effects of including material damping and the rate-dependant material properties at different shock loads. The results indicate that stiffeners configurations and shock loads affect greatly the overall performance of steel plates and sensitive to the materials data. Also, the numerical results can be used to obtain design guidelines of floating structures to enhance resistance of underwater shock damage, since explosive tests are costly and dangerous.